EFFECTS OF BREAST CARE ON NURSING MOTHERS TOWARDS ON PRODUCTIVITY OF BREAST MILK (BREAST MILK) - Sri Untari; Laily Himawati; Rizki Sahara (The Shine Cahaya Dunia Kebidanan, 2022)
Background: Breast milk is the best nutrient for babies, which is a fat emulsion in a solution of protein, lactose and minerals. Colostrum contained in breast milk on the first day to the 7th day after the mother gives birth, proven to be useful in increasing antibody levels in babies One way to increase the flow of breast milk in nursing mothers is with breast care. This study aims to find out the effect of breast care on the productivity of breast milk (breast milk) in nursing mothers. Method: The design of this study is quasy experiment with a one group pre-test approach  and posttes side-taking techniques with a total sampling of 15 respondents. Data collection tools using observation sheets. Statistical test with Wilcoxon test. Results: the results showed that before the breast milk productivity was carried out on average 7.5 ml and breast milk productivity after breast treatment the average value was 24.25 ml and statistical tests showed a value of ρ value of 0.001 (<0.05).  Conclusion: there is an effect of breast care on the productivity of breast milk (breast milk) in nursing mothers